2014
DOI: 10.1128/jvi.01007-14
|View full text |Cite
|
Sign up to set email alerts
|

A Substitution in the Transmembrane Region of the Glycoprotein Leads to an Unstable Attenuation of Machupo Virus

Abstract: Machupo virus (MACV) is the etiologic agent of Bolivian hemorrhagic fever (BHF). Utilizing a reverse-genetics system recently developed, we report the rescue of a rationally modified recombinant MACV containing a single mutation in the transmembrane region of the glycoprotein. Following challenge of susceptible mice, we identified a significant reduction in virulence in the novel virus. We also identified an instability leading to reversion of the single mutation to a wild-type genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
(42 reference statements)
4
13
0
Order By: Relevance
“…In some cases, it is also possible that IFNs and cytokines might actually help the host to control or limit NW JUNV or MACV infection, which might explain how certain patients recovered from infections. In agreement with this, we find that IFNs are critical to control JUNV and MACV infections in murine systems (22,23,55,56). It is also worth noting that in the case of LASV infection in an NHP model, an early peak of type I IFN production correlated with animal survival, whereas fatal infection was characterized by a lack of early type I IFN production (57).…”
Section: Discussionsupporting
confidence: 83%
“…In some cases, it is also possible that IFNs and cytokines might actually help the host to control or limit NW JUNV or MACV infection, which might explain how certain patients recovered from infections. In agreement with this, we find that IFNs are critical to control JUNV and MACV infections in murine systems (22,23,55,56). It is also worth noting that in the case of LASV infection in an NHP model, an early peak of type I IFN production correlated with animal survival, whereas fatal infection was characterized by a lack of early type I IFN production (57).…”
Section: Discussionsupporting
confidence: 83%
“…This is in line with the findings of previous studies performed by others and us, in which GPC was identified to be the major viral factor for the attenuation of the vaccine strain of JUNV (14,16,22). Consistent with our previous report, rMACV infection was lethal to IFN-␣␤/␥ R Ϫ/Ϫ mice (15,18). In contrast, the virological and pathological results clearly demonstrated that rMACV/Cd#1-GPC was avirulent in the IFN-␣␤/␥ R Ϫ/Ϫ mouse model, similar to the findings for the live-attenuated Cd#1 vaccine strain of JUNV.…”
Section: Figsupporting
confidence: 82%
“…However, the F438I mutation was unstable in vivo. MACV isolates reverting to the wild-type sequence (F438) were identified in mice that succumbed to MACV F438I infection (15). The importance of the F427I mutation in JUNV attenuation was also demonstrated in guinea pigs infected with JUNV.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Most recently, this model was used to demonstrate that a single point mutation in the transmembrane region of the GP2 glycoprotein is involved in the attenuation of JUNV strain Candid#1, the current vaccine used in Argentina for prevention of AHF [ 121 ]. These findings were recently repeated with MACV, and the same mutation leads to viral attenuation in the mouse model [ 146 ]. Thus, while not useful for pathogenesis or MCM development, immune intact neonatal mice can provide valuable insight in the factors contributing to the attenuation of NW arenaviruses.…”
Section: Arenavirus Animal Modelsmentioning
confidence: 86%